A Smart Control System Model for Pharmaceutical and Medical Equipment Storage Using Fuzzy Logic and IoT - Didi Rahmat Saputra; Fadhila Azzahra; Lahuddin; Ade Octaviansyah (Yayasan Kita Menulis, 2025)
The primary goal of this study is to develop an innovative Smart Control System designed to maintain optimal temperature and humidity levels within a medical storage environment. By integrating Fuzzy Logic with Internet of Things (IoT) technology, we aim to enhance/optimize environmental control. Our experimental approach involved constructing an IoT-based prototype utilizing an Arduino Uno board equipped with high-precision temperature and humidity sensors, and DHT22 components for automated temperature and humidity stabilization. A fuzzy logic algorithm was employed/utilized to analyze real-time sensor data and generate/produce adaptive control outputs in response to environmental fluctuations. This smart control system is expected to significantly enhance/make a significant contribution to medical inventory management by reducing product damage and ensuring the safety of medical supplies. This research paves the way for future advancements in applying advanced technology for environmental control in healthcare settingsKeywords: Smart Control System, Fuzzy Logic, Internet Of Things (IoT)